Assessment of the external contribution to Olea pollen levels in southeastern Spain. (15th July 2021) - Viney, A.; Nicolás, J.F.; Galindo, N.; Fernández, J.; Soriano-Gomis, V.; Varea, M.
Abstract: The province of Alicante (southeastern Spain) has a low density of olive trees; however, a substantial increase in the number of patients with allergic sensitization to Olea has been observed in recent years. The present work seeks to identify and quantify the transport of Olea pollen from other source regions, defining a new parameter called External Pollen Index (EPI). The second objective of the study was to determine Olea pollen exposure levels in Alicante city using a new method based on statistical percentiles and linear regression analysis. For these purposes, a study of daily and 2-hour average concentrations of Olea pollen combined with cluster analysis of 2-hour back-trajectories was carried out during the pollination period of 2010–2015. The annual levels of olive pollen recorded in Alicante showed a significant contribution from the Western Iberian Peninsula. Thus, the EPI is defined as the sum of the contributions of pollen transported by air masses from southwestern and northwestern Spain. The good linear correlation beetween the EPI and the APIn (R 2  = 0.818; p-value 0.013) suggests that the total contribution of pollen from western regions may be a good predictor of the annual concentration of Olea pollen registered in Alicante. It has been estimated that, in the absence of external contributions, the Olea pollen concentration at the study area would be around 1300 pollen grains⋅m −3 . Olea pollen exposure levels determined in Alicante were: Low (<20 pollen grains⋅m −3 ), Moderate (20–50 pollen grains⋅m −3 ), High (51–100 pollen grains⋅m −3 ) and Very High (>100 pollen grains⋅m −3 ). High and very high exposure levels were associated with northwestern and southwestern contributions, respectively. Future research should consider external contributions (EPI) in prediction models in order to get a better estimation of pollen levels and, consequently, improve the information provided to the allergic population. Highlights: Olea pollen from western regions contributed 57% to the annual concentration. Olea pollen exposure levels in Alicante were determined using a new simple method. The higher allergy risk for the population was due to western contributions.